Pemanfaatan Youtube Sebagai Media Pembelajaran Di Kelas VI Sekolah Dasar - I Gede Agus Arya Sudarmika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of digital technology has transformed learning at the elementary school level, including the utilization of Youtube as a learning media. This study aims to explore the effectiveness of using Youtube in Grade VI elementary school learning through a literature review of 20 articles published between 2021 and 2025. The research employed a qualitative thematic synthesis approach to examine best practices, challenges, and implementation strategies of Youtube in Grade VI classrooms. The findings indicate that Youtube can enhance students’ learning outcomes, interest, and motivation when used systematically and integrated with active learning models such as Project-Based Learning, Problem-Based Learning, or Flipped Classroom. The teacher’s role is crucial in ensuring the successful use of this media, including curating content, light editing, creating curriculum-based playlists, and facilitating post-video reflection and discussion. Challenges identified include technological access limitations, internet quality, device availability, and content safety and appropriateness. Therefore, the effective use of Youtube in elementary education requires teacher readiness, infrastructure support, and school policies that ensure a safe and conducive digital learning environment. Overall, this study emphasizes that Youtube has great potential as an effective learning media if integrated with appropriate pedagogical strategies and supported learning conditions.